Oral LPS Dosing Induces Local Immunological Changes in the Pancreatic Lymph Nodes in Mice - Kihl, Pernille (J Diabetes Res, 2019)
Lacking the initial contact between the immune system and microbial-associated molecular patterns (MAMPs), such as lipopolysaccharides (LPS), early in life, may be regarded as one of the causal factors of the increasing global increase in the incidence of autoimmune diseases, such as type 1 diabetes (T1D). Previously, a reduced incidence of T1D accompanied by dramatically increased abundances of both the mucin-metabolising bacterium Akkermansia muciniphila, and LPS-carrying Proteobacteria was observed, when vancomycin was given to pups of nonobese diabetic (NOD) mice. While the T1D incidence reducing effect of A. muciniphila has been shown in further studies, little is known as to whether the increased abundance of LPS-carrying bacteria also has a protective effect. Therefore, we fed NOD pups with Eschericia coli LPS orally from birth to weaning, which decreased the gene expressions of TNFα, IL-10, IL-6, IFNγ, IL-1β, IL-2, IL-4, and FoxP3 in the pancreatic lymph nodes, while the same gene expression profile in the spleen was unaffected. However, no significant difference in the incidence of T1D, gut microbiota composition, or ileum expression of the genetic markers of gut permeability, Claudin8, Occludin, Zonulin-1 (Tjp1), Claudin15, Muc1, and Muc2 were observed in relation to LPS ingestion. It is, therefore, concluded that early life oral E. coli LPS has an impact on the local immune response, which, however, did not influence T1D incidence in NOD mice later in life.